An Overview of Prospective Drugs for Type 1 and Type 2 Diabetes - Wu, Ping; Liu, Zhenyu; Jiang, Xiaohong; Fang, Hao (Current Drug Targets, 2020)
Aims: The aim of this study is to provide an overview of several emerging anti-diabetic molecules. Background: Diabetes is a complex metabolic disorder involving the dysregulation of glucose homeostasis at various levels. Insulin, which is produced by β-pancreatic cells, is a chief regulator of glucose metabolism, regulating its consumption within cells, which leads to energy generation or storage as glycogen. Abnormally low insulin secretion from β-cells, insulin insensitivity, and insulin tolerance lead to higher plasma glucose levels, resulting in metabolic complications. The last century has witnessed extraordinary efforts by the scientific community to develop anti-diabetic drugs, and these efforts have resulted in the discovery of exogenous insulin and various classes of oral anti-diabetic drugs. Objective: Despite these exhaustive anti-diabetic pharmaceutical and therapeutic efforts, long-term glycemic control, hypoglycemic crisis, safety issues, large-scale economic burden and side effects remain the core problems. Methods: The last decade has witnessed the development of various new classes of anti-diabetic drugs with different pharmacokinetic and pharmacodynamic profiles. Details of their FDA approvals and advantages/disadvantages are summarized in this review. Results: The salient features of insulin degludec, sodium-glucose co-transporter 2 inhibitors, glucokinase activators, fibroblast growth factor 21 receptor agonists, and GLP-1 agonists are discussed. Conclusion: In the future, these new anti-diabetic drugs may have broad clinical applicability. Additional multicenter clinical studies on these new drugs should be conducted.
Keywords: glucokinase activators